Kinerja Guru Bahasa Indonesia di Era Pandemi Covid - 19 di SMAN Kecamatan Tenayan Raya - Safitri, Devi; Sukenti, Desi (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2024)
Teachers play a crucial role in improving the quality of education, where their performance determines their professionalism in the world of education. This research aims to describe, analyze, and interpret the performance of Indonesian language teachers at SMAN Sekecamatan Tenayan Raya during the Covid-19 pandemic. A descriptive method with a quantitative approach is employed in this study. The research population includes all Indonesian language teachers in three secondary schools in Pekanbaru, namely SMAN 6, 10, and 11. A sample of 12 teachers was selected. Data were collected through online questionnaires using Google Form with a Likert scale to measure teachers' performance. The research findings indicate that the performance of Indonesian language teachers at SMAN Sekecamatan Tenayan Raya during the Covid-19 pandemic is quite high. This is evident from the recapitulation of teacher data on their performance, with the highest scores achieved in the categories of "very often" (SS) and "often" (S). Specifically, aspects such as work quality, speed/accuracy of work, initiative in work, work capacity, and communication show satisfactory results, with high percentages. These findings affirm that Indonesian language teachers have been able to overcome the challenges of teaching during the Covid-19 pandemic effectively. In this difficult situation, their performance has made a positive contribution to the learning process and demonstrated their resilience in facing unforeseen circumstances.